(untitled) (The Pakistan Development Review, 2007)
Engr. Dr. M. Akram Sheikh, Deputy Chairman, Planning Commission of Pakistan. Past Presidents of the Pakistan Society of Development Economists, Distinguished participants to the 23rd Annual Conference and General Meeting of the Society. Ladies and Gentlemen: It is indeed an honour and privilege for me to deliver the Presidential address at this prestigious forum. I am very well aware of my distinguished predecessors who have served as Presidents of this Society and I hope that I can during my tenure do justice to this responsibility. As you perhaps know yesterday we held the first Convocation of the Pakistan Institute of Development Economics and in the afternoon we launched the Golden Jubilee Celebrations to mark fifty years of its existence. I am sure that given the high regard and esteem with which we all hold the Pakistan Institute of Development Economics, members of the Society will share in the pride that we all feel on the award of 10 PhDs and one MPhil to students of the Institute and also join me in congratulating the Institute on the occasion of its Golden Jubilee. The plans are to hold the Golden Jubilee Celebrations in different parts of the country and we look forward to your active participation in these events.